O ironii jako figurze retorycznej i postawie moralnej (z odniesieniem do Wittlina i Kierkegaarda) - Szewczyk-Haake, Katarzyna (Przestrzenie Teorii, 2015)
In his work as a writer, Józef Wittlin searched for literature able to grant the   reader moral support, while at the same time being artistically successful. In his novel Salt of the Earth, the way to com-bine these two, to a certain extent contradictionary aims, is found in the use of irony. An analysis of the classical types of irony appearing in the novel (naive irony, irony of the sender, verbal irony) leads to the conclusion that each of those was remarkably modified by the author. As a result, the “ironical anthropology” created by Wittlin in his novel lacks any elements of simple moralizing or giving ready-made moral solutions, but brings a striking image of a human commu-nity, unified not by a common status, but by a common fate. In the novel, irony turns out to be not only a textual figure, but first and foremost a moral stance, approximate to that of Socrates as described by Kierkegaard. Thanks to this stance, Wittlin enthuses his readers with the longing for the ideal, shaping their moral sensibility, at the same time granting them the sovereignty to which the reader of a literary work should be entitled.